Parasitic myoma after supracervical laparoscopic histerectomy - Maurício Paulo Angelo Mieli; Ana Maria Sampaio Moreira Grell; Ricardo dos Santos Simões; Leandro Accardo de Mattos (University of São Paulo, 2013)
Parasitic myoma is a condition defined as a myoma of extrauterine nourishing. It may occur spontaneously or as a consequence of surgical iatrogeny, after myomectomy or videolaparoscopic supracervical hysterectomy, due to remaining residues of uterine tissue fragments in the pelvic cavity after morcellation. The authors describe two cases in which the patients were submitted to videolaparoscopic supracervical hysterectomy and uterine body removal through morcellation. The sites of development of the parasitic myomas were next to the cervix stump in Case 1, and next to the right round ligament in Case 2. These parasitic myomas were removed by videolaparoscopy. After myomectomies or videolaparoscopic supracervical hysterectomies followed by uterine fragments removal from the pelvic cavity through morcellation, meticulous searching for residues or fragments of uterine tissue is mandatory to prevent the occurrence of parasitic myomas.